Analisis Kelayakan Tarif Pelayanan Kapal Perintis Menggunakan Metode Cost Revenue Analysis (CRA) pada Kapal Latih Barombong di Wilayah 3T Sulawesi Tenggara - Rahmawati Djunuda; Samaluddin Samaluddin; Azhar Aras Mubarak; Riska Damayanti; Alfiah Alif; La Ode Lukman Saputra (Jurnal Kajian dan Penelitian Umum, 2026)
Southeast Sulawesi Province, as an archipelagic region, faces challenges in inter-island connectivity, particularly in disadvantaged, frontier, and outermost (3T) areas. Pioneer vessels play a crucial role in supporting passenger mobility and goods distribution; however, their operational sustainability largely depends on financial feasibility. This study aims to analyze the tariff feasibility of the Barombong Training Vessel using the Cost Revenue Analysis (CRA) method. A quantitative approach was employed by analyzing operational costs (fixed and variable costs) and revenues based on various load factor scenarios. The results indicate that at load factors of 60% and 80%, the CRA values were 0.72 and 0.96, respectively (<1), indicating that revenues were insufficient to cover operational costs. Consequently, the vessel's operation was not financially feasible and still required subsidies. Financial feasibility was achieved at load factors of 90% and 100%, where the CRA values exceeded 1, indicating that revenues were sufficient to cover operational costs and generate profits. Therefore, the load factor is a key determinant of the operational feasibility of pioneer vessels. Strategies to increase load factors, along with subsidy support policies under certain conditions, are necessary to ensure the sustainability of pioneer shipping services in 3T regions.